Consolidation of Brazilian public education in the state of Mato Grosso (1889-1908) - Vieira Campos Ferreira, Nilce; Montes Geles, Yesica Paola (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2019)
The aim of this article is to examine the strengthening of public education of Mato Grossobetween 1889-1908, through the analysis of government legislations described in the reports issued by those who were in charge of public education at that time. For this purpose, two leading questions were posed to guide the analysis: was there agreement between the defense of the modern public school and the school model established in Cuiabá, capital of the state of Mato Grosso?; and were the public schools in Cuiabá subsidized with adequate materials and infrastructure for the development of classroom activities? Both official historical sources and messages from state presidents, laws or decrees related to public primary education, and public education reports from 1889 to 1908 were used for this study. The study concluded that, in 1889, when the proclamation of the Republic of Brazil took place, problems such as precariousness and lack of resources for teaching, as well as lack of qualified professionals, persisted in schools in Mato Grosso. These obstacles were repeatedly exposed in the messages issued by the government.